Modern Tendencies in the Development of the Energy Industry (Texas Journal of Multidisciplinary Studies, 2022)
The article deals with renewable energy sources covering a number of different types of primary energy (solar energy, wind energy, biomass, water flows, geothermal heat, waste), the largest development rates in the world are currently achieved by China, India and the USA